1977
DOI: 10.1073/pnas.74.9.3947
|View full text |Cite
|
Sign up to set email alerts
|

Mutator action by Escherichia coli strains carrying dnaE mutations

Abstract: Several newly isolated temperature-sensitive dnaE mutants of Escherichia coli exhibit powerful mutagenic action at permissive temperatures. Mutation rates for the two most active mutants were assayed at four different temperatures and compared to wild-type behavior. Temperature-resistant revertants of the original temperature-sensitive dnaE mutants exhibited lower, nearly normal, mutation rates, but no antimutator strains were found.The appearance of new mutants in a population is an essential part of the evol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The in vivo experiments have suggested that indeed HE is highly accurate, as expected for the major replicating enzyme (Schaaper, 1993a). The importance of Pol III for controlling the mutation rate is also evidenced by the properties of several E. coli mutator mutants (which have enhanced mutation rates) carrying a defect in the dnaE gene encoding the Pol III a subunit (Sevastopoulos & Glaser, 1977;Fijalkowska et al, 1993;Oller et al, 1993;Vandewiele et al, 2002). Strong mutators have also been found residing in the dnaQ gene, encoding the e proofreading subunit (Fijalkowska & Schaaper, 1996;Taft-Benz & Schaaper, 1998), establishing the importance of the proofreading process for the chromosomal replication process.…”
Section: Dna Pol III Hementioning
confidence: 99%
“…The in vivo experiments have suggested that indeed HE is highly accurate, as expected for the major replicating enzyme (Schaaper, 1993a). The importance of Pol III for controlling the mutation rate is also evidenced by the properties of several E. coli mutator mutants (which have enhanced mutation rates) carrying a defect in the dnaE gene encoding the Pol III a subunit (Sevastopoulos & Glaser, 1977;Fijalkowska et al, 1993;Oller et al, 1993;Vandewiele et al, 2002). Strong mutators have also been found residing in the dnaQ gene, encoding the e proofreading subunit (Fijalkowska & Schaaper, 1996;Taft-Benz & Schaaper, 1998), establishing the importance of the proofreading process for the chromosomal replication process.…”
Section: Dna Pol III Hementioning
confidence: 99%
“…In Escherichia coli, mutator mutations mapping in the dnaE gene presumably affect nucleotide selection by DNA polymerase III (28). Mutations mapping in the dnaQ gene (also called mutD) affect the proofreading 3'->5' exonuclease function of the DNA polymerase III holoenzyme (6,8), whereas mutH, mutL, mutS, and mutU mutations cause defects in methyl-directed postreplicative mismatch correction (for reviews, see references 21 and 24).…”
mentioning
confidence: 99%
“…All of the mutator mutations so far described in Escherichia coli increase the frequency of point mutations (base-pair substitutions and frame-shift mutations). Thermosensitive mutations in dnaE cause erratic functioning of DNA polymerase III (dnaE gene product), which includes incorrect nucleotides (1). Mutations in dnaQ (mutD) decrease the proofreading activity of the DNA polymerase III holoenzyme (2), and mutations in mutH, mutL, mutS, and mutU affect the methyl-directed postreplicative mismatch correction (for review, see ref.…”
mentioning
confidence: 99%